(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the incidence of reported cases of schistosomiasis and the impact of the schistosomiasis control program’s actions in the states of the Northeast region of Brazil in the period 2010-2017. It was an epidemiological, cross-sectional and descriptive survey that used data obtained from the Schistosomiasis Control Program of the Brazilian Unified Health System. Between 2010 and 2017, 10,824 cases of schistosomiasis were reported in the Northeast region of the country, among which about 55% of those diagnosed are male, and are predominantly aged between 20-59 years. In parallel, there was a reduction in the number of confirmed cases and in the incidence of the bill of review, ranging from an incidence rate of 14.3% (2010) to 9.2% (2017). Schistosomiasis was found to be more prevalent in the following northeastern states: Bahia (52.9%), and Pernambuco (25.1%). The lowest prevalence was identified in the states of Ceará (2.45%), Rio Grande do Norte (2.05%), and Piauí (0.14%). According to data from the Schistosomiasis Control Program, there was a tendency to reduce positive cases, although it is essential to ensure access to therapy for these patients. Therefore, it is possible to affirm that the actions of the control programs have contributed expressively to the reduction of the rates of positivity of schistosomiasis in the endemic regions of Northeastern Brazil, however, the effort must be maintained so that Brazil no longer belongs to the list of endemic countries for this disease.